DNA barcoding relates Trichuris species from a human and a man’s best friend to non-human primate sources - Brandon-Mong, Guo Jie; Ketzis, Jennifer K.; Choy, J.S.; Boonroumkaew, Patcharaporn; Mahboob, Tooba; Sawangjaroen, Nongyao; Yasiri, Atipat; Janwan, Penchom; Tan, Tian Chye; Nissapatorn, Veeranoot (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Trichuris trichiura, the whipworm of humans, is one of the most prevalent soil-transmitted helminths (STH) reported worldwide. According to a recent study, out of 289 STH studies in Southeast Asia, only three studies used molecular methods. Hence, the genetic assemblages of Trichuris in Southeast Asia are poorly understood. In this study, we used partial mitochondrial DNA (cytochrome c oxidase subunit 1 or COI) sequences for analysis. Trichuris grouped in a same clade with different hosts indicate the potential of cross infection between hosts. Based on COI, the adult Trichuris isolated from a Malaysian patient was most closely related to Trichuris isolated from Papio anubis (olive baboons) from the USA. The Trichuris isolated from the dog from Malaysia was genetically similar to a Trichuris species isolated from Macaca silenus (lion-tailed macaque) from Czech Republic. Both the human and dog isolated Trichuris grouped in clades with different hosts indicating the potential of cross infection between hosts. Specific PCR primers based on the partial COI of T. trichiura isolated from African green monkey and T. serrata were designed and successfully amplified using multiplex PCR of the pooled DNA samples. Our results suggest a complex parasite-host relationship, and support the theory of cross infection of Trichuris between humans and non-human primates as suggested in previous publications.